EFL Students' Perceptions and Preferences Towards Written Corrective Feedback at Sintuwu Maroso University - Danali, Fellisia; Modjanggo, Vivin Krismawanti; Mamudi, Sitti Fitriawati (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This research aims to provide information regarding students' perceptions and preferences towards written corrective feedback given by lecturers in writing classes. This research uses a quantitative approach with a survey design. The data are collected from questionnaires. There are 61 EFL students’ participated in filling out the questionnaire. The research results show that: 1) EFL students’ perceptions of written correction feedback are based on their views or expectations of feedback, EFL students’ agree that feedback can help them write better next time. Based on experience with feedback, EFL students’ agree that feedback explains their mistakes in writing. Based on the usefulness or value of feedback, EFL students’ agree that feedback tells them how to make their writing better. Based on the affect or emotions associated with feedback, EFL students’ agree that feedback on their writing makes them feel confident. 2) The types of written corrective feedback that most preferred by EFL students’ are unfocused feedback, focused feedback, and direct feedback.